Islamisasi Ilmu Pengetahuan dalam Bingkai Integrasi-Interkoneksi: Menguak Ide Islamisasi Ilmu Ismail Raji Al-Faruqi - Raha Bistara (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2021)
This article intends to examine how the concept of integration-interconnection as a formula in overcoming the skeptical secularism out of the rationalism and empiricism. The Islamization of science that was initiated by Ismasil Raji al-Faruqi is a response from the secularism indication that have spread among Muslims, both at the economic, political, cultural and scientific levels. The spread of this concept within Muslims create malaism , which only accept all things what comes from the Western. Whereas Islam as a science religion has its own characteristics that are based on the principles of Qur'an and the Sunnah. The Contradiction of This epistemological is that Muslims should be able to rise up and resist the oppression carried out by Western with their secular concept. By using the library method, this research seeks to find the answer of knowledge problems accepted by Muslims by processing data sources, both primary and secondary sources. The primary source is the original work of Ismail Raji al-Faruqi, while the most important source of sekunder is in the form of supporting data related to this research. The data processing is expected to solve the problems in Muslims understanding with scientific integration-interconnection concept. These integration-interconnection have become a very important basis for finding two opposing scientific poles, that is Islamic and secular in nature.